The Modern Zoo: Demographics and Perceptions of Two International Groups of Zoo Staff - Heather Bacon; Belinda Vigors; Darren J. Shaw; Natalie Waran; Cathy M. Dwyer; Catriona Bell (Journal of Zoological and Botanical Gardens, 2021)
Characterising the people that work in zoos is a key element of understanding how zoos might better contribute to conservation activities. The purpose of this study was to investigate demographics, early life experiences and perceptions of zoo staff to the role of the modern zoo. This paper reports the key characteristics and qualitative themes emerging from study of international (European and Chinese) zoo professionals. Semi-structured telephone interviews were conducted with eight Chinese and eight European zoo staff about aspects of zoological animal welfare, conservation and zoological practices. These qualitative data were thematically analysed, and themes generated. This paper describes interviewee demographics and two themes relating to ‘early life influences’ and ‘the role of the modern zoo’. This analysis indicates that demographic data and early life influences of zoo professionals were broadly similar between two culturally diverse regions, but that their views on the role of the modern zoo differed, particularly in terms of their perceptions of conservation activities, with European interviewees focussing on biodiversity conservation, and Chinese interviewees focussing on animal protection.